THE ROLE OF THE NEW MARITIME ROUTE IN ENSURING CUSTOMS INTERESTS OF UKRAINE DURING FULL-SCALE WAR - PROKOPENKO, Valeriia; SMIRNOVA, Oleksandra; ZUBRYTSKYI, Artur (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article outlines the role of the new maritime route in enhancing the efficiency of implementing Ukraine's customs interests in the conditions of full-scale war.  Based on the problem of customs activities generated by the extreme reorientation of foreign trade flows from seaports to the western border. In particular, the effective implementation of customs interests was hindered by the following factors: insufficient staffing of veterinary and phytosanitary services at customs checkpoints in neighboring EU countries, increased import of passenger cars during the period of preferential customs clearance, and the absence of a fully functional system of joint customs control at border crossings between Ukraine and the EU. The purpose of the article is to characterize the new maritime route as a mechanism for reducing logistical pressure on customs authorities at the western border. The article also focuses on key indicators of the 'grain corridor' activity and its contribution to customs security. The features of the new maritime route's operation are described, and an assessment of the dynamics of its export capacity concerning the main cargoes is conducted. It is demonstrated that in December 2023 and January 2024, the indicators of export transshipment via this route practically reached pre-war levels and are highly likely to continue growing in the near future. Particular emphasis is placed on the need to increase the volumes of containerized and bulk cargo imports via the new maritime route, as this will contribute to diversifying import supplies and ensuring the stability of customs revenue inflows. It is also proposed to finalize agreements on joint customs control at border crossings with neighboring European countries, taking into account high security risks, including through the harmonization of Ukrainian and European customs legislation.
Keywords: logistics; 'grain corridor'; new maritime route; customs interests; export-import operations